Comparison of foot-and-mouth disease virus ’Asia 1’ field isolates and vaccine virus by plaque assay and plaque reduction neutralization test - MISHRA, N; RAI, D V; PATTINAIK, B (The Indian Journal of Animal Sciences, 2013)
Two field isolates of type ’Asia 1’ foot-and-mouth disease virus (FMDV) were compared were the homologous vaccine strain virus by plaque assay and plaque reduction-neutralization (PRN) test. The size: of the plaques formed by the vaccine strain virus and the field isolates varied from 2.5 mm in diameter. In PRN test, the dilutions of anti-146S guineapig serum (raised against the vaccine strain virus) causing 70% reduction in the number of plaques were found to be 870.40 (Â± 5.83), 409.60 (Â± 1.83), and 358.40 (Â± 1.53) for the vaccine strain virus and the two field isolates, respectively. This showed that the vaccine strain virus required lesser amount of antibodies than the two field isolales in causing 70% reduction in the number of plaques. However, the plaque reduction curves of these two field isolates showed no difference from that of the vaccine strain virus.